2010
DOI: 10.1177/0269216309356029
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing that it is part and parcel of what they do: teaching palliative care to medical students in the UK

Abstract: In their first year of work, newly qualified doctors will care for patients who have palliative care needs or who are dying, and they will need the skills to do this throughout their medical career. The General Medical Council in the United Kingdom has given clear recommendations that all medical students should receive core teaching on relieving pain and distress together with caring for the terminally ill. However, medical schools provide variable amounts of this teaching; some are able to deliver comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 22 publications
7
73
0
5
Order By: Relevance
“…Na formação médica atual, as escolas médicas deveriam contemplar a questão do ensino em cuidados no fim da vida em seus currículos de maneira a direcionar os futuros profissionais para o seu dia-a-dia e propiciar a fundamentação para a formação de generalistas com habilidades paliativistas. Revisão bibliográ-fica do Reino Unido demonstra que a maior preocupação dos coordenadores dos cursos médicos é promover a conscientização da medicina paliativa como especialidade aplicável a seus futuros pacientes 23 . A existência de profissional especialista em medicina paliativa como eixo integrador, mas não exclusivamente determinante desse ensino, parece necessária no contexto do ensino atual.…”
Section: Barreiras No Ensino Em Cuidados No Fim Da Vidaunclassified
“…Na formação médica atual, as escolas médicas deveriam contemplar a questão do ensino em cuidados no fim da vida em seus currículos de maneira a direcionar os futuros profissionais para o seu dia-a-dia e propiciar a fundamentação para a formação de generalistas com habilidades paliativistas. Revisão bibliográ-fica do Reino Unido demonstra que a maior preocupação dos coordenadores dos cursos médicos é promover a conscientização da medicina paliativa como especialidade aplicável a seus futuros pacientes 23 . A existência de profissional especialista em medicina paliativa como eixo integrador, mas não exclusivamente determinante desse ensino, parece necessária no contexto do ensino atual.…”
Section: Barreiras No Ensino Em Cuidados No Fim Da Vidaunclassified
“…13, 14 Medical school faculty focus on dispelling misconceptions and fears as well as developing positive attitudes toward students' future role in providing PC. 15 It has been reasoned that it is important to make students aware of their own attitudes toward death and dying: 16 ''rather than only attempting to create from undergraduates masters of pain and symptom control, teachers need to set out to develop their attitudes by creating a sensitive awareness of the needs of the dying and their families.'' 17 As Doyle has commented, ''What does it profit a doctor if he can prescribe opioids yet not know how to listen actively to those who need his help and humanity?…”
Section: Introductionmentioning
confidence: 99%
“…The skills needed in talking with patients and their families about life-limiting illness are more challenging to teach and learn, although recent years have seen significant developments in communication skills teaching. 19 Developing students' attitudes toward PC is of great importance 15 because attitudes predict future behavior; 20 positive attitudes toward hospice philosophy and care are associated with increased referrals for hospice care. 21 Lifetime attitudes are formed during the student years, 22 although some doctors report their brief exposure to PC as students were subsequently ''negated by the system.''…”
Section: Introductionmentioning
confidence: 99%
“…3,4 This document provides a clear framework for palliative care educators, but has been described as 'not achievable in already overloaded undergraduate curricula'. 5 The Scottish Government action plan for palliative care and the Department of Health end-of-life care programme both highlight the need for better education and training of all health professionals. 6,7 To inform the review of palliative care undergraduate medical curriculum and highlight potential areas for improvement, we surveyed FY1 doctors and supervising consultants in South East Scotland.…”
Section: Introductionmentioning
confidence: 99%
“…Ten years ago, Field and Wee, 11 and more recently Gibbins et al, 5 found that palliative care education varied considerably among UK medical schools, with some having very little dedicated teaching time and others with longer clinical placements. Our survey highlighted that a number of FY1 doctors had had little or no contact with dying patients or families during their clinical training.…”
mentioning
confidence: 99%